2018
DOI: 10.1111/jspn.12212
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic antibiotic serum concentrations by two blood collection methods within the pediatric patient: A comparative effectiveness trial

Abstract: Repeated venipunctures and fingersticks to confirm serum drug concentrations cause pain and dissatisfaction for pediatric patients and their families. In many organizations, the standard of care to obtain therapeutic serum drug concentrations by peripheral venipuncture or capillary fingerstick, even when the patient has an existing peripheral intravenous catheter (PIV) or central venous catheter (CVC). The primary objective of this study was to assess agreement between serum tobramycin/vancomycin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A waste sample was then collected before the therapeutic sample and the volume of the waste sample was also determined by the catheter type and size. The Rc value, the concordance correlation coefficient which reflects both accuracy and precision, for both tobramycin and vancomycin was 0.982, demonstrating good agreement between the two sample collection methods 41 . Based on these findings, none of the 36 samples collected from either CVC/PIV versus peripheral venipuncture/fingerstick would have required a clinically significant dose adjustment.…”
Section: Monitoring Parametersmentioning
confidence: 76%
“…A waste sample was then collected before the therapeutic sample and the volume of the waste sample was also determined by the catheter type and size. The Rc value, the concordance correlation coefficient which reflects both accuracy and precision, for both tobramycin and vancomycin was 0.982, demonstrating good agreement between the two sample collection methods 41 . Based on these findings, none of the 36 samples collected from either CVC/PIV versus peripheral venipuncture/fingerstick would have required a clinically significant dose adjustment.…”
Section: Monitoring Parametersmentioning
confidence: 76%
“…The venipuncture or capillary fingerstick might be considered painful and stressful. Lichlitter et al [146] conducted a study in which the blood samples were collected by existing central venous catheter (CVC) and peripheral intravenous catheter (PIV). The measurements were conducted for VAN and tobramycin in pediatric patients.…”
Section: Factors Affecting Serum Concentrations In Tdmmentioning
confidence: 99%
“…4,5 Recent studies have demonstrated substantial agreement in intravenous anti-pseudomonal antibiotic serum levels when collected by PV vs PICC in pediatric PwCF, suggesting that TDM by PICC may be acceptable. [6][7][8] Serum levels obtained by PV can cause pain, and patient dissatisfaction in both children and adults. [9][10][11][12] In addition, 2).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are concerns that intravenous antipseudomonal antibiotic serum levels may be falsely elevated when collected directly through a PICC 4,5 . Recent studies have demonstrated substantial agreement in intravenous anti‐pseudomonal antibiotic serum levels when collected by PV vs PICC in pediatric PwCF, suggesting that TDM by PICC may be acceptable 6–8 . Serum levels obtained by PV can cause pain, and patient dissatisfaction in both children and adults 9–12 .…”
Section: Introductionmentioning
confidence: 99%